Reconstruction of Confiscation of Corruption Convicts' Assets in Restitution of State Financial Losses Islamic Law Analysis - Najjar Alavi, Ivan; Marpaung, Watni; Harahap, Arifuddin Muda (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Corruption is an extraordinary crime that harms state finances and hinders national development. One of the main strategies in eradicating corruption is the confiscation of assets resulting from criminal acts to recover state losses. However, the implementation of asset confiscation in Indonesia still faces various obstacles, including ineffective regulations, complicated legal procedures, and weak coordination between law enforcement agencies. This study analyzes the main obstacles in the implementation of asset confiscation based on positive law and Islamic law and formulates a legal reconstruction that can increase the effectiveness of asset recovery from corruption. This study uses a normative legal method with a descriptive-analytical approach, comparing applicable regulations and their implementation in Indonesia. The results of the study indicate that asset confiscation is not optimal due to the difficulty of proving the origin of assets, the use of third parties in hiding assets, and the absence of a Non-Conviction Based Asset Forfeiture (NCB) mechanism. From an Islamic legal perspective, confiscation of assets resulting from crime is in line with the principles of justice and welfare, as emphasized in QS. Al-Baqarah: 188 and the hadith of the Prophet Muhammad SAW which requires the return of property resulting from injustice. As a recommendation, this study proposes the implementation of the NCB mechanism, strengthening international cooperation in asset tracking, reforming evidence by shifting the burden of proof, and optimizing the management of confiscated assets for the public interest according to the principle of maslahah in Islamic law. With this approach, it is hoped that asset confiscation can become a more effective instrument in eradicating corruption and restoring state finances.